Living with bariatric surgery : managing your mind and your weight - Ratcliffe, Denise (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2018)
Living with Bariatric Surgery: Managing Your Mind and Your Weight aims to help those who are considering bariatric surgery develop a psychological understanding of their eating behaviour and the changes needed in order to make surgery successful. It is also a resource for those who have undergone surgery to help them adapt to the physical, psychological and relationship adjustments that occur. Whilst the benefits of bariatric surgery are significant, the psychological challenges it presents for patients have been overlooked. This book will help patients develop a realistic view of bariatric surgery and the changes required. It incorporates the real-life experiences of people who have had bariatric surgery, showing how they have responded to the psychological and behavioural changes after surgery, and also features helpful psychoeducation, exercises and strategies to facilitate reflection and learning. Living with Bariatric Surgery will be an essential guide for anyone considering, preparing for or recovering from bariatric surgery, as well as mental health professionals working with these clients."--
part, I Getting ready for bariatric surgery / Ratcliffe Denise -- chapter Introduction / Ratcliffe Denise -- chapter 1 Developing a balanced and realistic view of bariatric surgery / Ratcliffe Denise -- chapter 2 Creating new habits and making changes in preparation for bariatric surgery / Ratcliffe Denise -- chapter 3 Understanding and managing your emotional relationship with food / Ratcliffe Denise -- chapter 4 Final steps before surgery / Ratcliffe Denise -- part, II Life after bariatric surgery / Ratcliffe Denise -- chapter 5 Life on the other side -- Adjusting to early life changes after bariatric surgery / Ratcliffe Denise -- chapter 6 Negotiating weight changes after bariatric surgeryThe honeymoon period and beyond / Ratcliffe Denise -- chapter 7 Negotiating your new relationship with food and managing pitfalls / Ratcliffe Denise -- chapter 8 Improving psychological wellbeing and managing psychological pitfalls after surgery / Ratcliffe Denise -- chapter 9 Physical activity / Ratcliffe Denise -- chapter 10 Body image and body confidence / Ratcliffe Denise -- chapter 11 Changes in relationships / Ratcliffe Denise -- chapter 12 Unmet weight loss expectations and weight regain after bariatric surgery / Ratcliffe Denise.
Keywords: Obesity -- Surgery -- Psychological aspects